Study protocol for a cluster randomized controlled trial to test "¡Míranos! Look at Us, We Are Healthy!" - an early childhood obesity prevention program - Zenong Yin; Sarah L. Ullevig; Erica Sosa; Yuanyuan Liang; Todd Olmstead; Jeffrey T. Howard; Vanessa L. Errisuriz; Vanessa M. Estrada; Cristina E. Martinez; Meizi He; Sharon Small; Cindy Schoenmakers; et al. (BMC, 2019)
Abstract Background One in three Head Start children is either overweight or obese. We will test the efficacy of an early childhood obesity prevention program, "¡Míranos! Look at Us, We Are Healthy!" (¡Míranos!), which promotes healthy growth and targets multiple energy balance-related behaviors in predominantly Latino children in Head Start. The ¡Míranos! intervention includes center-based (policy changes, staff development, gross motor program, and nutrition education) and home-based (parent engagement/education and home visits) interventions to address key enablers and barriers in obesity prevention in childcare. In partnership with Head Start, we have demonstrated the feasibility and acceptability of the proposed interventions to influence energy balance-related behaviors favorably in Head Start children. Methods Using a three-arm cluster randomized controlled design, 12 Head Start centers will be randomly assigned in equal number to one of three conditions: 1) a combined center- and home-based intervention, 2) center-based intervention only, or 3) comparison. The interventions will be delivered by trained Head Start staff during the academic year. A total of 444 3-year-old children (52% females; n = 37 per center at baseline) in two cohorts will be enrolled in the study and followed prospectively 1 year post-intervention. Data collection will be conducted at baseline, immediately post-intervention, and at the one-year follow-up and will include height, weight, physical activity (PA) and sedentary behaviors, sleep duration and screen time, gross motor development, dietary intake and food and activity preferences. Information on family background, parental weight, PA- and nutrition-related practices and behaviors, PA and nutrition policy and environment at center and home, intervention program costs, and treatment fidelity will also be collected. Discussion With endorsement and collaboration of two local Head Start administrators, ¡Míranos!, as a culturally tailored obesity prevention program, is poised to provide evidence of efficacy and cost-effectiveness of a policy and environmental approach to prevent early onset of obesity in low-income Latino preschool children. ¡Míranos! can be disseminated to various organized childcare settings, as it is built on the Head Start program and its infrastructure, which set a gold standard for early childhood education, as well as current PA and nutrition recommendations for preschool children. Trial registration ClinicalTrials.Gov (NCT03590834) July 18, 2018.